A compact, highly stable spectral shearing interferometer to accurately reconstruct ultrafast laser fields. (July 2020) - Cai, Yi; Chen, Zhenkuan; Zheng, Shuiqin; Shangguan, Huangcheng; Zeng, Xuanke; Lu, Xiaowei; Wang, Hongyu; Xu, Shixiang
Highlights: A compact design for reconstructing accurately ultrafast laser fields. Common-path interferometry can improve signal-to-noise ratio and stability. All-transmission pulse duplicator is more stable than Michelson interferometer. With Two-step-phase-shifting function for complex-pulse measurement. Abstract: This paper presents a compact design for spectral shearing interferometry to reconstruct an ultrafast electric-field (SPIDER) with a high signal-to-noise ratio (SNR) and stability. Compared experimentally with the traditional SPIDER based on a Michelson interferometer (MI), this design can improve the SNR by a factor of 3.7 in a 25 dB BW region. Using the material dispersions of 6 mm BK7 plates as a target, the phase errors between the measured and theoretical values are less than 2.6 mrad, which is improved by a factor of ~4 from 10.3 mrad measured with the MI-based version. Even for a 1 mm fused silica plate, the measured phase errors are less than 2.1 mrad from the calculated values. Using this design for a 3-day test of our ultrashort pulse laser system, the variation in the output pulse width from the first to the third day is only 1.5%. We attribute this excellent performance to the common-path and all-transmission design of the test pulse pair, giving the design superior capacity against external disturbances. Our design can also work with the two-step phase-shift (TSPS) method to improve its measurement of the plulses with complex temporal/spectral structures.